Elastic parallel chinlon and preparation process thereof

By using two-component juxtaposed composite fibers composed of nylon fibers of different crystallinity, the problem of fewer reports of composite fibers composed of polyamide fibers in the prior art is solved, and fiber preparation with high elasticity and good elastic recovery performance is achieved.

CN120119353APending Publication Date: 2025-06-10FUJIAN YONGRONG TECH INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510346300.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing two-component side-by-side composite fibers mainly use polyester, polyamide or polyolefin fibers. There are few reports of two-component side-by-side composite fibers composed of polyamides, and the high crystallinity of nylon leads to poor elasticity, flexibility and light transmission.

Method used

Two nylon fibers of different crystallinity are used to form elastic juxtaposition nylon, and fibers with two-component juxtaposition composite structure are formed by blending and heat treatment. The crystallinity of the first nylon fiber is 10 or more larger than that of the second nylon fiber.

Benefits of technology

Elastic juxtaposition fibers with good elasticity have good elastic recovery performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005324743870000081
    Figure BDA0005324743870000081
  • Figure BDA0005324743870000091
    Figure BDA0005324743870000091
Patent Text Reader

Abstract

The invention provides elastic parallel chinlon and a preparation process thereof, and relates to the technical field of composite fibers. The elastic parallel chinlon is composed of a first chinlon fiber and a second chinlon fiber, and the crystallinity of the first chinlon fiber is 10 or more larger than that of the second chinlon fiber. According to the invention, the difference value between the crystallinity of the first polyamide fiber and the crystallinity of the second polyamide fiber is controlled within a certain range, so that the elastic parallel fiber with better elastic property can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite fibers, and relates to an elastic conjugate polyamide fiber and its preparation process. Background Art

[0002] Polyamide fiber is a polyamide fiber, also known as nylon. Commonly used ones include nylon 6, nylon 66, nylon 610, nylon 1010, etc. Due to the strong hydrogen bond interaction within the molecule, it has a high crystallinity, high rigidity, good wear resistance, mechanical strength, self-lubrication, etc. The high rigidity and crystallinity result in poor elasticity, flexibility, and light transmittance of polyamide fiber, and it is not easy to process.

[0003] The bicomponent conjugate composite fiber is an elastic fiber with a three-dimensional crimp structure, which is composed of two fibers with good compatibility and large differences in thermal shrinkage properties. When the fiber is preheated again, due to the different thermal shrinkage rates of the two fibers, a permanent helical three-dimensional crimp structure will be formed, thereby endowing the composite fiber with good elastic elongation and elastic recovery properties.

[0004] Currently reported fibers used in bicomponent conjugate composite fibers include polyester, polyamide, or polyolefin, etc. However, there are few reports on bicomponent conjugate composite fibers composed entirely of polyamide. Summary of the Invention

[0005] The inventor of the present invention unexpectedly found that an elastic conjugate polyamide fiber with better elasticity can be obtained by using two polyamide fibers with different crystallinities, rather than two or more fibers with different existing thermal shrinkage rates. Based on this, the present invention provides an elastic conjugate polyamide fiber and its preparation process.

[0006] The technical solution of the present invention is as follows:

[0007] An elastic conjugate polyamide fiber is composed of a first polyamide fiber and a second polyamide fiber;

[0008] The crystallinity of the first polyamide fiber is 10 or more greater than that of the second polyamide fiber.

[0009] Preferably, the crystallinity of the first polyamide fiber is 15 or more greater than that of the second polyamide fiber.

[0010] Preferably, the crystallinity of the first polyamide fiber is not less than 30.

[0011] Preferably, the crystallinity of the first polyamide fiber is 30 - 45, and the crystallinity of the second polyamide fiber is not less than 15.

[0012] Preferably, the crystallinity of the first polyamide fiber is higher than 45 and not exceeding 60, and the crystallinity of the second polyamide fiber is not less than 25.

[0013] Preferably, the crystallinity of the first polyamide fiber is higher than 60, and the crystallinity of the second polyamide fiber is not less than 30.

[0014] Preferably, the first polyamide resin used for the first polyamide fiber contains an aromatic group or a cycloalkyl group.

[0015] Preferably, the second polyamide resin used for the second polyamide fiber does not contain an aromatic group and a cycloalkyl group.

[0016] Preferably, the weight ratio of the first polyamide fiber to the second polyamide fiber is 3:7 - 7:3.

[0017] A preparation process of an elastic conjugate polyamide is that the first polyamide resin and the second polyamide resin are blended and heat-treated to form an elastic conjugate polyamide with a two-component conjugate composite structure;

[0018] The first polyamide resin forms the first polyamide fiber;

[0019] The second polyamide resin forms the second polyamide fiber;

[0020] The crystallinity of the first polyamide fiber is 10 or more greater than the crystallinity of the second polyamide fiber.

[0021] The beneficial effect of the present invention is that the elastic conjugate fiber composed of two polyamide fibers with different crystallinities and a crystallinity difference of not less than 10 has good elasticity, good elastic recovery performance, and good elastic stability. Specific Embodiments

[0022] The technical solutions of the present invention are further described and illustrated below through specific embodiments.

[0023] In order to obtain an elastic conjugate fiber with good elasticity, on the one hand, the present invention provides an elastic conjugate polyamide composed of a first polyamide fiber and a second polyamide fiber;

[0024] The crystallinity of the first polyamide fiber is 10 or more greater than the crystallinity of the second polyamide fiber.

[0025] Polyamides can range from amorphous to crystalline according to their structure, and the crystallinity can even be as high as 70% or more. Crystallinity has a great influence on the mechanical properties of polyamides. Mechanical strengths such as tensile strength, flexural strength, and flexural modulus all increase with the increase in crystallinity, while flexibility and elasticity decrease with the increase in crystallinity. In the prior art, elastic conjugate fibers are generally prepared by blending fibers with good compatibility and different thermal shrinkage rates, and then obtaining elastic conjugate fibers with good elasticity through heat treatment. The present invention discovers that by using a combination of two polyamides with different crystallinities and both crystallinities > 0, the compatibility between the polyamides is good, and the difference in crystallinity is not less than 10. Blending and heat treatment can also obtain elastic conjugate fibers with better elastic properties.

[0026] In the present invention, there is no particular limitation on the method for testing crystallinity. For example, X-ray diffraction method (XRD), differential scanning calorimetry (DSC), nuclear magnetic resonance method (NMR), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, etc. One of these methods can be selected for testing. Taking XRD as an example, the area of the crystallization peak S c and the area of the amorphous peak S nc are measured. Crystallinity = S c / (S c +S nc )×100%. Factors affecting the crystallinity of polyamides include not only the structure, composition, molecular weight, molecular weight distribution, and additives (such as nucleating agents) of polyamides, but also crystallization conditions such as crystallization temperature, crystallization time, crystallization pressure, annealing conditions, and drawing speed. Generally, the higher the crystallization temperature, the lower the crystallinity; the longer the crystallization time, the higher the crystallinity; the slower the drawing speed, the higher the crystallinity. Therefore, for elastic conjugate fibers, the crystallinity of the fibers can be adjusted by adjusting the materials, crystallization temperature, crystallization time, drawing rate, etc. of the two polyamide fibers, and then an elastic conjugate fiber composed of two polyamide fibers with different crystallinities can be obtained. When the materials and blending process of the two polyamide fibers are determined, the crystallinity of the two fibers can be adjusted by adjusting the heat treatment (i.e., heat setting) temperature to produce a difference in crystallinity. For the same polyamide material, such as nylon 66, the crystallinity can be adjusted between 20 - 60 depending on different crystallization conditions. For example, the crystallinity of the first polyamide fiber can be above 30, such as 30, 32, 35, 37, 40, 43, 45, 47, 50, 55, 60, etc.; for example, when the crystallinity of the first polyamide fiber is 35, the crystallinity of the second polyamide fiber can be 25, 22, 20, 18, 15, 12, 10, etc. Further, the crystallinity of the second polyamide fiber is not less than 5, or further still, not less than 10.

[0027] In some embodiments, the crystallinity of the first polyamide fiber is 15 or more greater than that of the second polyamide fiber. For example, when the crystallinity of the first polyamide fiber is 35, the crystallinity of the second polyamide fiber can be 20, 18, 15, 12, 10, etc.; when the crystallinity of the first polyamide fiber is 45, the crystallinity of the second polyamide fiber can be 30, 32, 30, 27, 25, 22, 20, 16, etc.

[0028] In some embodiments, the crystallinity of the first polyamide fiber is not less than 30. For example, the crystallinity of the first polyamide fiber can be 30, 32, 35, 37, 40, 43, 45, 47, 50, 55, 60, 65, 70, etc.

[0029] In some embodiments, the crystallinity of the first polyamide fiber is 30 - 45, and the crystallinity of the second polyamide fiber is not less than 15. The present invention further finds that when the crystallinity of the first polyamide fiber is 30 - 45, the crystallinity of the second polyamide fiber should not be less than 15, otherwise the crystallinity difference between the two polyamide fibers is too large, which is also not conducive to obtaining elastic conjugate fibers with good elastic properties. For example, the crystallinity of the first polyamide fiber and the second polyamide fiber can be 30 and 15, 35 and 15, 40 and 20, 40 and 18, etc.

[0030] In some embodiments, the crystallinity of the first polyamide fiber is higher than 45 and not more than 60, and the crystallinity of the second polyamide fiber is not less than 25. The present invention further finds that when the crystallinity of the first polyamide fiber is 45 (excluding 45) - 60, the crystallinity of the second polyamide fiber should not be less than 25, otherwise the crystallinity difference between the two polyamide fibers is too large, which is also not conducive to obtaining elastic conjugate fibers with good elastic properties. For example, the crystallinity of the first polyamide fiber and the second polyamide fiber can be 47 and 25, 50 and 25, 55 and 25, 55 and 25, 60 and 27, 60 and 30, etc.

[0031] In some embodiments, the crystallinity of the first polyamide fiber is higher than 60, and the crystallinity of the second polyamide fiber is not less than 30. The present invention further finds that when the crystallinity of the first polyamide fiber is higher than 60, the crystallinity of the second polyamide fiber should not be less than 30, otherwise the crystallinity difference between the two polyamide fibers is too large, which is not conducive to obtaining elastic conjugate fibers with good elastic properties. For example, the crystallinity of the first polyamide fiber and the second polyamide fiber can be 62 and 30, 62 and 32, 62 and 35, 65 and 36, 65 and 40, 70 and 40, etc.

[0032] In some embodiments, the first polyamide resin used for the first polyamide fiber contains an aromatic group or a cycloalkyl group. The structure of the first polyamide fiber contains an aromatic group or a cycloalkyl group. For example, the raw material dicarboxylic acid compound can be terephthalic acid, etc., and the diamine compound can be p-phenylenediamine, etc. The obtained polyamide fiber can be, for example, poly(p-phenyleneterephthalamide), poly(p-phenylenetadodecanediamide), poly(p-phenylenetetradecanediamide), poly(p-phenylenedecanediamide), poly(hexamethyleneterephthalamide), poly(octamethyleneterephthalamide), etc. It has higher rigidity and is more conducive to obtaining elastic conjugate fibers with better elastic properties after heat treatment. Further, the first polyamide resin is preferably a semi-aromatic or semi-cycloalkyl polyamide, that is, only one of the raw material dicarboxylic acid compound and diamine compound contains an aromatic group or a cycloalkyl group, to avoid the first polyamide fiber having too high rigidity and being not conducive to processing.

[0033] In some embodiments, the second polyamide resin used for the second polyamide fiber does not contain an aromatic group and a cycloalkyl group. The structure of the second polyamide resin does not contain an aromatic group and / or a cycloalkyl group, and the second polyamide fiber has better flexibility. Due to the difference in flexibility between the first polyamide fiber and the second polyamide fiber, it is conducive to further improving the elastic conjugate fibers with better elastic properties obtained after heat treatment.

[0034] In some embodiments, the weight ratio of the first polyamide fiber to the second polyamide fiber is 3:7 - 7:3. For example, the weight ratio can be any value among 3:7, 1:2, 4:6, 3:4, 5:5, 4:3, 6:4, 2:1, 7:3, etc., without particular limitation.

[0035] On the other hand, the present invention also provides a preparation process for elastic conjugate polyamide, which is formed by blending and heat-treating the first polyamide resin and the second amide resin to form elastic conjugate polyamide with a two-component conjugate composite structure;

[0036] The first polyamide resin forms the first polyamide fiber;

[0037] The second polyamide resin forms the second polyamide fiber;

[0038] The crystallinity of the first polyamide fiber is 10 or more greater than the crystallinity of the second polyamide fiber.

[0039] In the present invention, there are no particular limitations on the raw material compositions of the first polyamide resin and the second polyamide resin. In addition to the polyamide resin, it may also contain a nucleating agent, an antioxidant, a heat-resistant additive, an anti-ultraviolet agent, a pigment, etc. There are no particular limitations on the polyamide resin, and it can be directly obtained from commercially available products, such as PA46, PA6, PA66, PA1010, PA6T, PA6T / 66, PA610, PA12, PA9T, etc., or it can also be a nylon elastomer, a bio-based polyamide resin, etc. Taking the nucleating agent as an example, adding a nucleating agent can increase the crystallization rate and crystallinity of the polyamide resin. It can be an inorganic nucleating agent, an organic nucleating agent, a composite nucleating agent, etc. For example, the inorganic nucleating agent can be nano-silica, nano-aluminum oxide, nano-ZrO 2 , nano-ZnO, nano-MgO, etc., the organic nucleating agent can be an amide, a polycarbonate, a carbon fiber, a fatty acid salt, etc., and the composite nucleating agent is composed of two or more different nucleating agents compounded. The nucleating agent can also be directly obtained from commercially available products, such as Clariant CAV102, NAV101, SN15 / 106 from Sanhe Chemical Industry, CH22 from Dongguan Chuangzhiyuan, etc. For example, when a nucleating agent is added to the first polyamide fiber and not added to the second polyamide fiber, there can be a relatively obvious difference in the crystallinity formed during crystallization; or by adjusting the heat treatment temperature, for example, the heat treatment temperature is 30°C lower than the crystallization temperature of the first polyamide fiber, but the heat treatment temperature is only 5°C lower than the crystallization temperature of the second polyamide fiber, which is more conducive to the first polyamide fiber obtaining a higher crystallinity.

[0040] Assume that the crystallization temperature (such as the cooling crystallization temperature) of the first polyamide resin is T1, and the crystallization temperature (such as the cooling crystallization temperature) of the second polyamide resin is T2. If T1>T2, then the above heat treatment temperature T is lower than T2, and T can be (T2 - 5)°C, (T2 - 10)°C, (T2 - 15)°C, (T2 - 20)°C, etc.; if T1≤T2, then the above heat treatment temperature is lower than T1, and T can be (T1 - 5)°C, (T1 - 10)°C, (T1 - 15)°C, (T1 - 20)°C, etc. That is, in the present invention, the heat treatment temperature is lower than the cooling crystallization temperatures of both the first polyamide resin and the second polyamide resin. The purpose of the heat treatment is to promote the crystallization of the first polyamide fiber and the second polyamide fiber and form a difference in crystallinity.

[0041] The elastic conjugate fibers of the present invention can be widely used in the production of various textile fabrics, especially suitable for woven and knitted denim fabrics, elastic fabrics, stretch shirts, suits and trousers, stretch women's clothing, summer T-shirts and women's fashions, etc. It can also be interwoven with various other fibers to obtain more novel fabrics with different styles, further improving the quality and performance of clothing fabrics and meeting the needs of modern people for a quality life.

[0042] The technical solutions of the present invention will be further described and illustrated according to the following embodiments. Unless otherwise specified, the parts mentioned in the following embodiments are parts by weight.

[0043] In the following examples and comparative examples, the first polyamide resin and the second polyamide resin are as follows:

[0044] First polyamide resin ①: PA46.

[0045] First polyamide resin ②: PA6T / 66.

[0046] First polyamide resin ③: PA66.

[0047] Second polyamide resin ①: PA1010.

[0048] Second polyamide resin ②: PA6.

[0049] Second polyamide resin ③: PA610.

[0050] In the following examples, the blending is carried out by a two-component composite spinning machine. The diameters of the main and auxiliary screws are both 30 mm, the length-diameter ratio is 25:1, the diameter of the spinneret holes is 0.25 mm, the number of holes is 24, the spinning speed is 1200 m / min, and the drawing ratio is 2.5.

[0051] Example 1

[0052] The first polyamide resin ① and the second amide resin ① are melted at 295°C and 200°C respectively, and then blended at a weight ratio of 1:1, and heat-fixed at 170°C for 50 s to form an elastic side-by-side polyamide with a two-component side-by-side composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ① and the second amide resin ①, and both the first polyamide resin ① and the second amide resin ① crystallize.

[0053] Example 2

[0054] The first polyamide resin ① and the second amide resin ② are melted at 295°C and 260°C respectively, and then blended at a weight ratio of 1:1, and heat-fixed at 160°C for 50 s to form an elastic side-by-side polyamide with a two-component side-by-side composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ① and the second amide resin ②, and both the first polyamide resin ① and the second amide resin ② crystallize.

[0055] Example 3

[0056] The first polyamide resin ① and the second polyamide resin ③ are melted at 295° C. and 220° C. respectively, and then blended at a weight ratio of 1:1, and heat-fixed at 95° C. for 50 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ① and the crystallization temperature of the second polyamide resin ③, and both the first polyamide resin ① and the second polyamide resin ③ are crystallized.

[0057] Example 4

[0058] The first polyamide resin ① and the second polyamide resin ③ are melted at 295°C and 220°C respectively, and then blended in a weight ratio of 1:1, and heat-fixed at 160°C for 50s to form an elastic parallel nylon with a two-component parallel composite structure. When the heat-fixing temperature is lower than the cooling crystallization temperature of the first polyamide resin ①, the first polyamide resin ① crystallizes; when the heat-fixing temperature is higher than the cooling crystallization temperature of the second polyamide resin ③, the second polyamide resin ③ does not crystallize.

[0059] Example 5

[0060] The first polyamide resin ② and the second amide resin ① are melted at 310° C. and 200° C. respectively, and then blended at a weight ratio of 2:1, and then heat-fixed at 165° C. for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ② and the crystallization temperature of the second amide resin ①, and both the first polyamide resin ② and the second amide resin ① are crystallized.

[0061] Example 6

[0062] The first polyamide resin ② and the second amide resin ② are melted at 310° C. and 260° C. respectively, and then blended at a weight ratio of 2:1, and then heat-fixed at 165° C. for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ② and the crystallization temperature of the second amide resin ②, and both the first polyamide resin ② and the second amide resin ② are crystallized.

[0063] Example 7

[0064] The first polyamide resin ② and the second polyamide resin ③ are melted at 310° C. and 220° C. respectively, and then blended at a weight ratio of 2:1, and heat-fixed at 92° C. for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ② and the crystallization temperature of the second polyamide resin ③, and both the first polyamide resin ② and the second polyamide resin ③ are crystallized.

[0065] Example 8

[0066] The first polyamide resin ③ and the second amide resin ① are melted at 260° C. and 200° C. respectively, and then blended at a weight ratio of 1:2, and then heat-fixed at 135° C. for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ③ and the crystallization temperature of the second amide resin ①, and both the first polyamide resin ③ and the second amide resin ① are crystallized.

[0067] Example 9

[0068] The first polyamide resin ③ and the second polyamide resin ② are melted at 260° C. and 260° C. respectively, and then blended at a weight ratio of 1:2, and then heat-fixed at 135° C. for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ③ and the crystallization temperature of the second polyamide resin ②, and both the first polyamide resin ③ and the second polyamide resin ② are crystallized.

[0069] Example 10

[0070] The first polyamide resin ③ and the second amide resin ③ are melted at 260° C. and 220° C. respectively, and then blended at a weight ratio of 1:2, and then heat-fixed at 93° C. for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ③ and the crystallization temperature of the second amide resin ③, and both the first polyamide resin ③ and the second amide resin ③ are crystallized.

[0071] Embodiment 11

[0072] The second polyamide resin ② and the second amide resin ③ were melted at 260°C and 220°C respectively, and then blended in a weight ratio of 1:2, and then heat-fixed at 96°C for 55 seconds to form an elastic parallel nylon with a two-component parallel composite structure. The heat-fixing temperature is lower than the crystallization temperature of the first polyamide resin ② and the crystallization temperature of the second amide resin ③, and the second polyamide resin ② and the second amide resin ③ both crystallize.

[0073] The crystallinity X of the first nylon fiber formed by the first polyamide resin and the second amide resin in the elastic parallel nylon in the above Examples 1-11 is measured by DSC. c1 and the crystallinity X of the second nylon fiber c2 .

[0074] The breaking strength is tested by an electronic single yarn strength meter;

[0075] The curl shrinkage and curl stability are tested according to the method of GB / T 6506-2017.

[0076] The results are shown in Table 1 below.

[0077] Table 1

[0078]

[0079]

[0080] As can be seen from the data in Table 1 above, the present invention obtains elastic conjugate polyamide by blending two kinds of crystalline polyamide fibers, and has good elastic properties. It can be seen from Example 4 that when the first polyamide fiber is crystalline and the second polyamide fiber is amorphous, the elastic properties of the obtained elastic conjugate fiber are not good. It can be seen from Example 8 that when the crystallinity difference between the first polyamide fiber and the second polyamide fiber is less than 10, the elastic properties of the obtained elastic conjugate fiber are not good enough. By comparing Examples 7 and 11, it can be seen that when the heat setting temperature is increased, the crystallinity of both the first polyamide fiber and the second polyamide fiber decreases, and the crystallinity of the first polyamide fiber decreases more significantly, resulting in the crystallinity of the first polyamide fiber being lower than 30, and the elastic properties of the obtained elastic conjugate fiber are not good.

[0081] As described above, the basic principles, main features and advantages of the present invention have been shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments are only preferred embodiments of the present invention. The scope of the present invention cannot be limited thereby. That is, equivalent changes and modifications made according to the scope of the present invention patent and the content of the specification should still fall within the scope covered by the present invention. The scope of protection required by the present invention is defined by the appended claims and their equivalents.

Claims

1. An elastic parallel nylon, characterized in that: Composed of a first nylon fiber and a second nylon fiber; The crystallinity of the first nylon fiber is greater than that of the second nylon fiber by 10 or more.

2. The elastic parallel nylon according to claim 1, characterized in that: The crystallinity of the first nylon fiber is greater than that of the second nylon fiber by 15 or more.

3. The elastic parallel nylon according to claim 1 or 2, characterized in that: The crystallinity of the first nylon fiber is not less than 30.

4. The elastic parallel nylon according to claim 1 or 2, characterized in that: The crystallinity of the first nylon fiber is 30-45, and the crystallinity of the second nylon fiber is not less than 15.

5. The elastic parallel nylon according to claim 1 or 2, characterized in that: The crystallinity of the first nylon fiber is higher than 45 and not more than 60, and the crystallinity of the second nylon fiber is not less than 25.

6. The elastic parallel nylon according to claim 1 or 2, characterized in that: The crystallinity of the first nylon fiber is higher than 60, and the crystallinity of the second nylon fiber is not lower than 30.

7. The elastic parallel nylon according to claim 1 or 2, characterized in that: The first polyamide resin used for the first nylon fiber contains an aromatic group or a cycloalkyl group.

8. The elastic parallel nylon according to claim 1 or 2, characterized in that: The second polyamide resin used for the second nylon fiber does not contain aromatic groups and cycloalkyl groups.

9. The elastic parallel nylon according to claim 1 or 2, characterized in that: The weight ratio of the first nylon fiber to the second nylon fiber is 3:7-7:

3.

10. A process for preparing elastic parallel nylon, characterized in that: The elastic parallel nylon with a two-component parallel composite structure is formed by blending a first polyamide resin and a second polyamide resin and subjecting the blend to heat treatment; The first polyamide resin forms a first nylon fiber; The second polyamide resin forms a second nylon fiber; The crystallinity of the first nylon fiber is greater than that of the second nylon fiber by 10 or more.